A study on the effect of using the video teach-back method in continuous nursing care of stroke patients - Wang, Fei; Feng, Wen-Ming; Zhu, Ming; Sun, Qi; Zhang, Yong-Mei; Wang, Bing; Luo, Xiao-Yong; Shen, Jian-Tong; Fang, Xiao-Wei; Zhang, Ting; Cui, Ge (Frontiers in Public Health, 2024)
Objective: To explore the effect of the video teach-back method on continuous family nursing care of stroke patients. Methods: Stroke patients who met the criteria hospitalised in our hospital between March 2020 and March 2023 were randomly divided into the intervention group (n = 45), which received routine health education plus caregiver video teach-back training, and the control group (n = 45), which received routine health education only. The nursing effect was compared between the two groups. Results: Compared with the baseline, the total score for the caring ability of caregivers in the intervention group increased significantly over time and was higher than that in the control group. The caring burden score of caregivers in the intervention group decreased significantly over time and was lower than that in the control group. Conclusion: The teach-back method combined with video education improves the nursing ability of family caregivers and can improve the self-care ability of stroke patients.